Analisis Pertumbuhan Tanaman serta Komponen Hasil Kedelai Edamame pada Berbagai Dosis dan Waktu Aplikasi Pupuk Hayati di Tanah Gambut - Muliandari, Nadya; Zulfita, Dwi; Safriadi; Sitorus, Dermawati (Politeknik Negeri Lampung, 2025)
Edamame soybean grows in tropical and subtropical climates. Indonesia's climate conditions are suitable for the growth of edamame in temperatures around 22 - 32oC and rainfall between 1.000 – 5.000 mm/year. Edamame also able to adapt in the conditions of high organic matter land such as peat soil. Attempt to improve peat soil productivity is by providing biofertilizers containing microbes to increase soil fertility. The timing of biofertilizer application is related to the effectiveness of nutrient absorption by plants. This research aims to obtain the interaction of dosage and time of biofertilizer application on the morphophysiological characteristics and yield of edamame soybean on peat soil. This research conducted from May – September 2024 at Bansir Darat village, Southeast Pontianak Subdistrict. A factorial Randomized Block Design was implemented in this research, consisting of three replications and two experimental factors including the dosage of biofertilizer (D) namely d1 = 50 kg / ha, d2 = 75 kg / ha and d3 = 100 kg / ha; the second factor is time of biofertilizer application (W) namely w1 = 2 and 4 WAP (Weeks After Planting) and w2 = 2, 4 and 6 WAP. The results of this research obtained the interactions at various dosages and application times on the analysis of plant growth and edamame soybean yield components on peat soil. The interaction of biofertilizer at dosage of 75 kg/ha and the application time of biofertilizer 2 and 4 WAP provided the best analysis of plant growth and edamame yield components on peat soil. Keywords: Biofertilizer, Edamame Soybean, Peat.